The Cohesion and Coherence of the Editorials in The Jakarta Post - Prayudha, Prayudha (Universitas Ahmad Dahlan, 2016)
Concept of discourse involves three dimensions that are as language use, communication of beliefs (human cognition), and interaction in social situation. As a language use, discourse consists of two elements: cohesion and coherence. Discourse is divided into spoken and written discourse. Written discourse such as newspaper is very familiar today. One of the famous newspapers in Indonesia is The Jakarta Post. The most essential article in a newspaper is its editorial. Therefore, the research has been intended to find cohesion and coherence devices of the editorials in The Jakarta Post. In this research, substantive data were texts consisting of cohesion and coherence devices. The sources were editorials in The Jakarta Post May 2011 edition that consisted of 28 editorial articles. The data was analyzed using Identity Method. Results of the analysis showed that editorials in The Jakarta Post May 2011 contain all kinds of cohesion and coherence devices. The editorials contain grammatical cohesion (reference, ellipsis, substitution, conjunction) and lexical cohesion (reiteration and collocation). Coherence devices (repetition, personal reference, transition) are also contained in the data.